Micropropagation of Artocarpus heterophyllus LAM. and assessment of genetic stability using ISSR markers - Mustafa Kamal, Nurul Husna (2015)
Jackfruit (Artocarpus heterophyllus) is a multi-purpose species that provides the source of food, timber, fuel, fodder, medicinal and industrial products. The plant, however, is mostly known for its edible fibrous medium-sized fruit which is crunchy, juicy and sweet. Jackfruit can be propagated through seeds and vegetative means. However, the seeds are known for its recalcitrant nature, thus it cannot be stored outside for a long period of time. Thus, this study was carried out in order to produce uniform planting materials in large quantity using in vitro technique. Micropropagation has been proven to successfully mass produce plantlets in a short time as well as producing disease-free plantlets. In the experiment on optimization of seed sterilization procedure, the whole seeds were sterilized with 70% ethanol for 1 min followed by different concentrations (30, 40 and 50%) of Clorox® (5.25% sodium hypochlorate) for 20 min and rinsed once with sterile distilled water. This was followed by immersion in 10, 20 and 30% Clorox® for 15 min then rinsed five times with sterile distilled water. Tween 20 was added into the Clorox® solution as surfactant. The seeds were successfully sterilized using 40% Clorox for 20 min + 20% Clorox for 15 min and 50% Clorox for 20 min followed by 20% Clorox for 15 min. For the effect of different concentrations of hormones on shoot regeneration from seeds, aseptic seeds were cultured on half-strength MS medium supplemented with different concentrations (0, 1.0, 2.5, 5.0, 7.5 and 10.0 mg/L) of BAP and KIN separately. BAP at 2.5 mg/L was chosen as the most suitable concentration producing a mean number of 7.33 shoots. Shoot induction using shoot tip and different node positions (node 1 and node 2) of seed derived shoots showed that there were no significant differences on mean number of shoots produced per explant between the node positions. Nevertheless, node 2 gave the highest mean number of shoots (4.47). For the effect of decapitation on shoot regeneration of in vitro shoots there was significant difference between the decapitated and non-decapitated shoots on mean number of shoots produced per explant. The mean number of shoots for the decapitated shoots reached 12.73. In the shoot multiplication experiment, node 1 and node 2 were cultured on half-strength MS medium supplemented with 3 different cytokinin types at 5 different concentrations each; BAP (1.0, 2.5, 5.0, 7.5 and 10.0 mg/L), KIN (1.0, 2.5, 5.0, 7.5 and 10.0 mg/L) and TDZ (0.05, 0.1, 0.5, 1.0 and 2.0 mg/L). BAP at 1.0 mg/L gave the highest mean number of shoots (17.13). BAP at 5.0 mg/L, on the other hand, gave the highest mean shoot length (2.95 cm). BAP at 1.0 mg/L however was chosen as the most suitable treatment in producing multiple shoots. For rooting of shoots, shoots which were 5 – 6 cm in length were separated individually and placed on half-strength MS medium containing different concentrations (0, 1.0, 2.5 and 5.0 mg/L) of IBA and NAA separately. Medium containing 2.5 mg/L IBA gave the highest mean number of roots (18.73). The control however had the highest mean root length (3.37 cm). Nevertheless, 2.5 mg/L IBA was chosen as the best treatment for rooting. The completely rooted plantlets were tested on 4 different potting mixtures which were organic soil and topsoil (1:1), perlite and sand (1:1), peat moss and sand (1:1) and organic matter, topsoil and sand (1:1:1). The acclimatized plantlets were observed to perform best in potting medium containing organic soil and topsoil (1:1). The percentage of plantlet survival was 88.89%. ISSR markers were used to assess the genetic stability of the regenerants at the fifth subculture and it was observed that some of the regenerants evaluated showed variability compared to the mother plant. Out of 19 regenerants assesed, 15 had Jacaard’s similarity coefficient of 1.0000, signifying that nearly 80% of the regenerants were identical to the mother plant. From this study, it can be concluded that in vitro technique can be used as a suitable means of propagating clonal A. heterophyllus in large quantity. Moreover, the propagules produced exhibited high genetic stability even at the fifth subculture.